An exploration of the occurrence of speech sound disorders in children with autism spectrum disorder aged 4;0 ? 7;11 years - Kapoutsis, Stefania (Department of Health and Rehabilitation Sciences, 2024)
Language development in children with autism spectrum disorder (ASD) is an area of study that has received a lot of attention, however there is limited research available on speech development in this population. There is especially limited research that has investigated speech sound disorders (SSDs) in children with ASD in South Africa. This study aimed to describe the type of SSDs children with Autism Spectrum Disorders (ASD) aged 4;0 – 7;11 years present with. The study employed a descriptive, exploratory research design. Twentyfive children aged 4;0 – 7;11 years with a diagnosis of ASD, attending English-medium schools in the Southern Suburbs of Cape Town, South Africa, participated in the study. The findings were described based on the classifications of SSDs (using Dodd's (2005) differential diagnostic framework), intelligibility ratings, production of phonemes and phonotactic structures, the occurrence of phonological processes, oro-motor ability, and prosody. Phonological delays were the most commonly occurring SSDs, this was followed by articulation disorders, phonological disorders and inconsistent phonological disorders. No participants in the sample were diagnosed with childhood apraxia of speech (CAS). The findings suggested that children with ASD appear to acquire vowels, consonants and phonotactic structures at the same trajectory as typically developing children. Variations in the acquisition of fricatives, affricates and liquids were observed. Substitution, syllable and atypical phonological processes were observed across the sample. A higher prevalence of delayed and atypical phonological processes were observed in the sample of children with ASD, compared to the norms available for typically developing children. The results of this study have indicated that while children with ASD acquire phonemes at the same rate as their typically developing peers, children with ASD may be more likely to present with SSDs. These findings highlight the need for SLTs to ensure that accurate speech assessments are carried out among this population, rather than focusing solely on language. This study is a starting point for further research to be carried out on speech development and SSDs in children with ASD.